Model Peningkatan Kinerja Melalui Motivasi Kerja Sebagai Intervening Karyawan PT. Incasi Raya Padang - Yulina Eliza; Yass Andria; Irwan Muslim (Universitas Batanghari Jambi, 2022)
The survey conducted turned out to be the low performance of PT. Incasi Raya Padang. This is certainly influenced by several factors, including the work environment, work discipline and work motivation. This study aims to see the influence of: a) The influence of the work environment, work discipline on employee work motivation. b). The influence of work motivation, work environment and work discipline on employee performance. c). The influence of the work environment and work discipline on the performance of PT. Incasi Raya Padang with work motivation as an intervention. The population and samples in this study were employees of PT. Incasi Raya Padang as many as 60 people. Sample determination using total sampling. Data processing using Path Analysis. The results of this study show that the work environment has a significant effect on employee motivation. Work discipline has no significant effect on employee motivation. Motivation has a significant effect on employee performance. The work environment does not have a significant effect on the performance of PT. Incasi Raya Padang. Work discipline has a significant effect on the performance of PT. Incasi Raya Padang. Indirectly, the work environment (X1) through motivation (Y) has a significant effect on employee performance. Indirectly, work discipline through motivation has an insignificant effect on PT. Incasi Raya Padang. The advice that can be conveyed in this study is for PT. Incasi Raya Padang can pay attention to employee comfort at work, because this is seen from the results of surveys and respondents' results on the work environment, it still shows poor results. Employee discipline must be prioritized and improved, so as to increase work motivation which has an impact on improving employee performance in carrying out tasks. Giving awards to employees in the form of position promotion can increase work motivation, so that it has a direct impact on employee performance.